0
$\begingroup$

I'm reading Nakahara GEOMETRY, TOPOLOGY AND PHYSICS now.Then, Hodge Laplacian is given by \begin{align} \Delta=(d+d^{\dagger})^2=dd^{\dagger}+d^{\dagger}d \end{align} For example, we consider 0-form $f$, then $d^{\dagger}f=0$ \begin{align} \Delta f&=d^{\dagger}df=d^{\dagger}(\partial_{\mu}f dx^{\mu})\\ &=-\ast d \ast(\partial_{\mu}f dx^{\mu})=-\ast d(\frac{\sqrt{|g|}}{(m-1)!}\partial_{\mu}f g^{\mu \lambda}\epsilon_{\lambda \nu_2 \cdot \nu_m} dx^{\nu_2}\wedge \cdots \wedge dx^{\nu_m})\\ &=-\ast \frac{1}{(m-1)!}\partial_{\nu}[\sqrt{|g|}g^{\mu \lambda} \partial_{\mu}f] \epsilon_{\lambda \nu_2 \cdot \nu_m} dx^{\nu}\wedge dx^{\nu_2}\wedge \cdots \wedge dx^{\nu_m} \end{align} So far, so good, but I don't understand the next transformation. \begin{align} \Delta f&=-\ast \partial_{\nu}[\sqrt{|g|}g^{\mu \lambda} \partial_{\mu}f] g^{-1} dx^1\wedge \cdots \wedge dx^m\\ &=-\frac{1}{\sqrt{|g|}}\partial_{\nu}[\sqrt{|g|}g^{\mu \lambda} \partial_{\mu}f] \end{align} Why did $g^{-1}$ come up? I would appreciate it if you could tell me. For your information, $\ast$ is defined as follows. \begin{align} \ast (dx^{\mu_1}\wedge dx^{\mu_2}\wedge \cdots \wedge dx^{\mu_r})=\frac{\sqrt{|g|}}{(m-r)!}\epsilon^{\mu_1\mu_2 \cdots \mu_r}\ _{\nu_{r+1}\cdots \nu_{m}}dx^{\nu_{r+1}}\wedge \cdots \wedge dx^{\nu_{m}} \end{align} where $m$ is just dimension of manifold.

$\endgroup$
0
$\begingroup$

Let's start with this expression,

$-\ast \frac{1}{(m-1)!}\partial_{\nu}[\sqrt{|g|}g^{\mu \lambda} \partial_{\mu}f] \epsilon_{\lambda \nu_2 \cdots\nu_m} dx^{\nu}\wedge dx^{\nu_2}\wedge \cdots \wedge dx^{\nu_m}.$

Now,

\begin{equation} \ast dx^{\nu}\wedge dx^{\nu_2}\wedge \cdots \wedge dx^{\nu_m}=\sqrt{|g|}\epsilon^{\nu\nu_2\cdots\nu_m}. \end{equation}

Therefore, the first expression becomes,

\begin{equation} \frac{1}{(m-1)!}\partial_{\nu}[\sqrt{|g|}g^{\mu \lambda} \partial_{\mu}f] \epsilon_{\lambda \nu_2 \cdots\nu_m}\sqrt{|g|}\epsilon^{\nu\nu_2\cdots\nu_m} \end{equation}

Using equation (7.171b) of the book, we can express the Levi Civita tensor with all contravariant indices in terms of the tensor with all covariant indices, \begin{equation} \frac{1}{(m-1)!}\partial_{\nu}[\sqrt{|g|}g^{\mu \lambda} \partial_{\mu}f] \epsilon_{\lambda \nu_2 \cdots\nu_m}\sqrt{|g|}g^{-1}\epsilon_{\nu\nu_2\cdots\nu_m}=\frac{1}{(m-1)!}\partial_{\nu}[\sqrt{|g|}g^{\mu \lambda} \partial_{\mu}f] \frac{1}{\sqrt{|g|}}(m-1)!\delta_{\lambda}^{\nu}. \end{equation} The second expression follows from a property of the Levi Civita tensor (see Wikipedia). This gives the desired expression.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.